2008
DOI: 10.1007/s10709-008-9249-7
|View full text |Cite
|
Sign up to set email alerts
|

Condition-dependence, genotype-by-environment interactions and the lek paradox

Abstract: The lek paradox states that maintaining genetic variation necessary for 'indirect benefit' models of female choice is difficult, and two interrelated solutions have been proposed. 'Genic capture' assumes condition-dependence of sexual traits, while genotype-by-environment interactions (GEIs) offer an additional way to maintain diversity. However, condition-dependence, particularly with GEIs, implies that environmental variation can blur the relationship between male displays and offspring fitness. These issues… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
89
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(92 citation statements)
references
References 34 publications
(36 reference statements)
2
89
1
Order By: Relevance
“…On the contrary, the intensity of female preference for bright male image was weak in July when conspicuous males were abundant. Some theoretical studies predict that there is plasticity in female mate preference, and females prefer rare male phenotypes (Kokko and Rankin 2006;Kokko and Heubel 2008). Results of this study seem to be consistent with these predictions.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…On the contrary, the intensity of female preference for bright male image was weak in July when conspicuous males were abundant. Some theoretical studies predict that there is plasticity in female mate preference, and females prefer rare male phenotypes (Kokko and Rankin 2006;Kokko and Heubel 2008). Results of this study seem to be consistent with these predictions.…”
Section: Discussionsupporting
confidence: 89%
“…However, some recent theoretical studies predict the plasticity in female preferences (Kokko and Rankin 2006;Kokko and Heubel 2008). If female preferences consistently favor some males having exaggerated ornaments over others, male ornaments will be exaggerated with a greater degree that are exposed to high predation risks or require more resources for production and maintenance of the traits.…”
Section: Introductionmentioning
confidence: 99%
“…Whilst G 9 E may contribute to the maintenance of genetic variation under selection (thus solving the ''lek paradox''), it also presents the problem that parent phenotypes may be poor predictors of offspring phenotypes and genotypes. This may weaken selection favouring mate choice on the basis of traits expressing G 9 E (Greenfield and Rodríguez 2004;Mills et al 2007;Bussière et al 2008;Kokko and Heubel 2008;Ingleby et al 2010). In light of this problem, our finding of relatively high heritabiliy and relatively weak G 9 E in genitalia suggests that the dynamics of sexual selection may be more stable for genitalia than for other types of sexual trait.…”
Section: Discussionmentioning
confidence: 83%
“…Under fluctuating environmental selection pressures, parental mating decisions should be to assure diversity within offspring, but will result in some proportion of offspring being maladapted to the future pathogen community (i.e. genetic bet-hedging; [63,64]). At the genomic level, it has been previously suggested that both natural and sexual selection may be driving the evolution of intermediate levels of diversity as a result of trade-offs between inbreeding Bet-hedging for MHC diversity M. L. Evans et al 383 and outbreeding depression [22,65 -67].…”
Section: Discussionmentioning
confidence: 99%